Design and Evaluation of Losartan Potassium Controlled Release Microcapsules - Suryadevara, Dr. Vidyadhara (Asian Journal of Pharmaceutics (AJP), 2022)
Objective: The objective of the present work is to formulate and evaluate Losartan potassium (LP) controlled release microcapsules using gum karaya and polyethylene oxide as polymers, sodium alginate, and calcium chloride as encapsulating material and cross-linking agent. Materials and Methods: LP controlled release microcapsules were prepared by ionic gelation method. The prepared microcapsules were characterized by flow properties such as angle of repose, compressibility index, particle size, and encapsulation efficiency and drug release profiles. Results: All the prepared microcapsules were spherical and exhibited good flow properties. LP is an antihypertensive drug which comes under the class of angiotension antagonist and it was greatly encapsulated with gum karaya and polyethylene oxide (Water soluble resin 303). The Fourier transform infrared spectroscopy and differential scanning calorimetry studies were conducted for pure drug, polymers and optimized formulations, the studies revealed that they were no incompatibilities between drug and polymers used in the present study. Scanning electron microscopy analysis showed that the microcapsules were uniform and spherical in nature with good surface characteristics. Among all the LP controlled release microcapsule formulations. Conclusions: The optimized formulation (L14) prepared with equal proportion of polymers gum karaya and polyethylene oxide was found to extend the release of drug up to 12 h.